2022
DOI: 10.3390/cells11020187
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNAs and Long Non-Coding RNAs in Sarcopenia

Abstract: Sarcopenia is an age-related pathological process characterized by loss of muscle mass and function, which consequently affects the quality of life of the elderly. There is growing evidence that non-coding RNAs, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), play a key role in skeletal muscle physiology. Alterations in the expression levels of miRNAs and lncRNAs contribute to muscle atrophy and sarcopenia by regulating various signaling pathways. This review summarizes the recent findings reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 116 publications
(187 reference statements)
0
16
0
Order By: Relevance
“…The data presented above show the importance of miRNAs and lncRNAs in the pathophysiology of sarcopenia. In fact, these transcripts can modulate the activity of a number of signaling pathways that are involved in the determination of muscle strength and function, including TGF‐β/BMP, IGF‐1, and MRF‐related signaling pathways (J. Lee & Kang, 2022). Although dysregulation of noncoding RNAs in the sarcopenic subjects has been elucidated by several studies, the molecular mechanisms employed by these transcripts in the context of aging‐related sarcopenia are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented above show the importance of miRNAs and lncRNAs in the pathophysiology of sarcopenia. In fact, these transcripts can modulate the activity of a number of signaling pathways that are involved in the determination of muscle strength and function, including TGF‐β/BMP, IGF‐1, and MRF‐related signaling pathways (J. Lee & Kang, 2022). Although dysregulation of noncoding RNAs in the sarcopenic subjects has been elucidated by several studies, the molecular mechanisms employed by these transcripts in the context of aging‐related sarcopenia are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented above show the importance of miRNAs and lncRNAs in the pathophysiology of sarcopenia. In fact, these transcripts can modulate the activity of a number of signaling pathways that are involved in the determination of muscle strength and function, including TGF-β/BMP, IGF-1, and MRF-related signaling pathways (J Lee & Kang, 2022)…”
mentioning
confidence: 99%
“…In the blood, alterations to the arsenal of cytokines, chemokines, and growth factors actively released by muscle cells, can be further explored for diagnosis of sarcopenia [ 108 ] or other muscle conditions. GDF-15 can feature in that scheme, in combination with other circulating stress-related factors inversely associated with muscle mass and function, including inducible heat shock protein 70 [ 109 , 110 ] and specific non-coding RNAs [ 111 ]. The search for susceptibility genes is another powerful tool to weigh the importance of the many factors involved in muscle disease, and genome-wide association studies in older individuals can identify gene variants that associate with muscle weakness [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing stream of research suggests that miRNAs have a big role in skeletal muscle physiology by targeting and preventing the translation of specific mRNAs. Research has found that miR-127 and miR-434-3p were generally downregulated in most aged mouse muscles ( Lee and Kang, 2022 ). Additionally, miR-101 was associated with frailty syndrome ( Carini et al, 2022 ) and Alzheimer’s disease ( Barbato et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%